Pengaruh Daya Ledak Tungkai, Koordinasi Mata Tangan dan Percaya Diri Terhadap KemampuancShooting dalam Permainan Bolabasket pada Atlit Bolabasket SMA Negeri 1 Sidrap - Muh Said Hasan (Seminar Nasional LP2M UNM, 2022)
Abstract. This study is a type of ex-post facto research that uses a path analysis research design. The population was all basketball Athletewith a total sample of 30 students. The technique used in determining the sample was positive sampling. The data analysis techniques used are descriptive analysis, requirements test, path analysis through the SPSS 20.00 program at a significant level of 95% or α 0.05. The results of the study reveal that (1) there is a direct influence of legs explosive power on self-confidence of basketball Athlete at SMA Negeri 1 Sidrap with a beta value of 0.502 with a significant level of 0.000<α0.05; (2) there is a direct influence of hands-eyes coordination on self-confidence of basketball Athlete at SMA Negeri 1 Sidrapwith a beta value of 0.494 with a significant level of 0.000<α0.05; (3) there is a direct influence of legs explosive power on basketball shooting skills of Athlete at SMA Negeri 1 Sidrap with a beta value of 0.280 with a significant level of 0.046<α0.05 (4) there is a direct influence of hands-eyes coordination on shooting skills in basketball games of extracurricular basketball Athlete at SMA Negeri 1 Sidrap with a beta value of 0.304 with a significant level of 0.030<α0.05; (5) there is a direct influence of self-confidence on shooting skills of basketball Athlete at SMA Negeri 1 Sidrap with a beta value of 0.415 with a significant level of 0.023<α0.05; (6) there is an influence of legs explosive power through self-confidence on shooting skills of basketball Athlete at SMA Negeri 1 Sidrap with a beta value of 0.208; and (7) there is an influence of hands-eyes coordination through self-confidence on shooting skills of basketball Athlete at SMAN 1 Sidrap with a beta value of 0.205. Keywords: Legs Explosive Power, Hands-Eyes Coordination, Self-Confidence, Basketball Shooting Skills